New directions in the analysis of inequality and poverty - Stephen P. Jenkins; John Micklewright (Institute for the Study of Labor (IZA), 2007)
Over the last four decades, academic and wider public interest in inequality and poverty has grown substantially. In this paper we address the question: what have been the major new directions in the analysis of inequality and poverty over the last thirty to forty years? We draw attention to developments under seven headings: changes in the extent of inequality and poverty, changes in the policy environment, increased scrutiny of the concepts of 'poverty' and 'inequality' and the rise of multidimensional approaches, the use of longitudinal perspectives, an increase in availability of and access to data, developments in analytical methods of measurement, and developments in modelling.
urn:nbn:de:101:1-20080401165
Keywords: 330; Einkommensverteilung; Armut; Sozialforschung; Welt